Schools as agents of cultural transmission and social control - LAOUIRA, Omar (Journal of Human Sciences, 1999)
During the development of sociology of education, there have been a move from macro questions of education and social change, and from the notion of input-output of people in education, to a greater concern with problems of curriculum change, teacher-pupil relationship, the formation of pupil identities, in other words to the complex question of how culture is transmitted through schools. This shift is precisely dated from the publication of Knowledge and control (1971), edited by M.F.D Young (Williamson, 1979, P10). In this essay, which concern the transmission of culture in schools, I have started it by a brief definition of the concept of "culture". The second point deals with the relation that emerges between culture and education. The third step is an outline of the theories of Pierre Bourdieu and Basil Bernstein. They are considered as the theorists of cultural transmission. The final paragraph is dealing with the principles that govern the selection of transmittable knowledge.